Constitutional Parameters of Judicial Activism in the Indonesian Constitutional Court - Faisyah, Nur; Safa'at, Muchamad Ali; Susmayanti, Riana (IJBLE Scientific Publications Community Inc., 2025)
This study examines the evolving role of Indonesia's Constitutional Court, specifically the tension between its constitutional mandate as a negative legislator and instances of judicial activism approaching positive legislation. Using normative legal research methodology, the research analyzes two landmark decisions, No. 90/PUU-XXI/2023 and No. 62/PUU-XXII/2024, to distinguish between legitimate constitutional review and potential judicial overreach. The findings reveal that while judicial activism can strengthen constitutional checks and balances when properly constrained, it risks undermining democratic legitimacy when extending to the creation of new legal norms. The study proposes a five-parameter framework emphasizing constitutional supremacy, compelling justification, substantive justice conditions, procedural integrity, and institutional restraint to guide judicial interpretation within constitutional boundaries. This framework contributes to resolving the fundamental challenge of balancing judicial independence with democratic accountability in Indonesia's evolving constitutional landscape, ensuring the Court can effectively safeguard constitutional rights without compromising democratic processes.